Easing Renegotiation Rules in Public Procurement: Evidence from a Policy Reform - Kris De Jaegher; Michal Šoltés; Vitezslav Titl (CESifo GmbH, 2024)
Public procurement contracts require frequent renegotiation. We exploit the Czech implementation of an EU policy as a natural experiment to investigate the effect of eased renegotiation rules. We document that the eased renegotiation rules decreased winning bids but did not change the final price: the extra renegotiated price compensates for the lower winning bids. We next develop a stylized theoretical model to explain these results. Finally, we provide suggestive evidence of changes in contract allocation, but find no evidence of any reduction in the quality of the delivered objects.
Keywords: H57; D44; D73; 330; public procurement; renegotiation; contracts